Recurrent miscarriage and fetal congenital malformations: Is there a neglected causal association?. (May 2020) - Visconti, D.; Neri, C.; De Santis, M.; Sabusco, G.P.; Gratta, M.; Campagna, G.; Lanzone, A.; Scambia, G.; Di Simone, N.
Abstract: Objective: The aim of the present study is to investigate the correlation between pregnancies complicated by morphological or chromosomal fetal anomalies and an obstetric history of two or more pregnancy losses, analyzing the association with any maternal risk factor. Study Design: Retrospective analysis of women who had access to the Day Hospital Clinic of Fondazione Policlinico Universitario A. Gemelli IRCCS in Rome from 2012 to 2018 for a pregnancy complicated by fetal malformation and/or abnormal karyotype, and who had an obstetric history of at least one pregnancy loss. Patients were divided into four groups depending on the number of miscarriages and the presence of a genetic anomaly: Group 0 included women with <2 miscarriages and fetal malformations, Group 1 included women with ≥2 miscarriages and fetal malformations, Group 2 included women with <2 abortion, fetal malformations and the presence of genetic anomalies; Group 3 included women with 2 ≥ abortions, fetal malformations and genetic anomalies. Statistical analysis was performed using the SAS v. 9.4 (SAS Institute Inc., Cary, NC, USA). Results: A total of 466 patients were included in the present analysis. Out of these, 379 patients belonged to Group 0; 40 patients entered in Group 1; Group 2 included 42 patients, and 5 patients were part of Group 3. Pregnancies complicated by fetal congenital malformations in patients with two or more pregnancy losses were significantly associated with maternal trombophilic disease and previous birth defects. Recurrent miscarriage and fetal structural anomalies were also significantly correlated with advanced maternal age. Conclusions: An adequate periconceptional counseling regarding the risk of fetal congenital anomalies may be indicated in patients affected by thrombophilic disease, as well as in those of advanced maternal age and with a pregnancy history of fetal malformations. The screening for thrombophilia may be advisable in patients with an obstetric history of congenital birth defects.